1, 25-Dihydroxyvitamin D3 stimulates odontoblastic differentiation of human dental pulp-stem cells in vitro. (2nd November 2017) - Mucuk, Goksen; Sepet, Elif; Erguven, Mine; Ekmekcı, Ozlem; Bılır, Ayhan
ABSTRACT: Background : 1, 25-Dihydroxyvitamin D3 (1, 25-OH D3 ) plays an important role in mineralized tissue metabolism, including teeth. However, few studies have addressed its role in odontoblastic differentiation of human dental pulp-stem cells (hDPSCs). Aim : This study aimed to understand the influence of various concentrations of 1, 25-OH D3 on the proliferation capacity and early dentinogenesis responses of hDPSCs. Materials and Methods: hDPSCs were obtained from the impacted third molar teeth. Monolayer cultured cells were incubated with a differentiation medium containing different concentrations of 1, 25-OH D3 (0.001, 0.01, and 0.1 µM). All groups were evaluated by S-phase rate [immunohistochemical (IHC) bromodeoxyuridine (BrdU) staining], STRO-1 and dentin sialoprotein (DSP)+ levels (IHC), and alkaline phosphatase (ALP, enzyme-linked immunosorbent assay (ELISA)) levels. Results : The number of cells that entered the S-phase was determined to be the highest and lowest in the control and 0.001 µM 1, 25-OH D3 groups, respectively. The 0.1 µM vitamin D3 group had the highest increase in DSP+ levels. The highest Stro-1 levels were detected in the control and 0.1 µM 1, 25-OH D3 groups, respectively. The 0.1 µM 1, 25-OH D3 induced a mild increase in ALP activity. Conclusions : This study demonstrated that 1, 25-OH D3 stimulated odontoblastic differentiation of hDPSCs in vitro in a dose-dependent manner. The high DSP + cell number and a mild increase in ALP activity suggest that DPSCs treated with 0.1 μM 1, 25-OH D3 are in the later stage of odontoblastic differentiation. The results confirm that 1, 25-OH D3 -added cocktail medium provides a sufficient microenvironment for the odontoblastic differentiation of hDPSCs in vitro.